2022
DOI: 10.3390/ijms231810480
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Properties of Linen Fibers and Dressings

Abstract: In antiquity, flax was used as a dressing for healing wounds. Currently, work is underway on the genetic modification of flax fibers to improve their properties. Genetic modifications have resulted in an increased content of antioxidants and more favorable mechanical properties. The works published so far have presented independent tests of fibers and dressings after appropriate technological treatments in cell cultures. This study aimed to compare the properties of the fibers and the dressing produced in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…With the aim of finding useful tools from natural sources, Gębarowski et al [ 5 ] investigated the benefits of wound dressings made from flax fibers and observed that they are efficacious in the promotion of tissue regeneration.…”
mentioning
confidence: 99%
“…With the aim of finding useful tools from natural sources, Gębarowski et al [ 5 ] investigated the benefits of wound dressings made from flax fibers and observed that they are efficacious in the promotion of tissue regeneration.…”
mentioning
confidence: 99%
“…Figure2. Flowchart of the effect on cell invasiveness of LoVo and LoVo/DX lines using the SPLS-car™ Scratcher cell migration assay system adapted with permission from Ref [37]…”
mentioning
confidence: 99%